Pre-bending a dynamic compression plate significantly alters strain distribution near the fracture plane in the mid-shaft femur. (May 2020) - Ristow, Jacob; Mead, Matthew; Cordeiro, Minal; Ostrander, James; Atkinson, Theresa; Atkinson, Patrick
This study evaluated the effect of pre-bending dynamic compression plates on fracture site compression. Recommendations of 1 to 2 mm of pre-bend have been proposed, but there does not appear to be experimental data to confirm the optimal pre-bend magnitude. Dynamic compression plating was performed on the lateral convex surface of 18 femoral analogs to fixate a simulated mid-shaft fracture. Plates with 0 mm (flat plate), 1 mm, and 2 mm of pre-bend were evaluated for their production of compression by determining the strain magnitudes for 10 equal-sized zones across the anterior cortex at the osteotomy site using digital imaging correlation. The 0 and 1 mm plates produced significantly more compression at the near cortex (p = 0.001 and p = 0.003, respectively) than the 2 mm plate. However, the 0 and 1 mm plates also created visible diastasis at the far cortex, while the 2 mm plate exhibited compression across all zones. The strain magnitudes for the 0 mm (R 2 = 0.62) and 1 mm (R 2 = 0.86) plates linearly and significantly decreased from the region adjacent to the plate until a region 50%–60% across the analog diameter. In contrast, the 2 mm plate exhibited uniform strains across the osteotomy site. This study demonstrates that pre-bending a dynamic compression plate 2 mm prior to fixation on a convex lateral femur provides the most compression at the far cortex. It also produces more uniform compression across the fracture when compared to 0 and 1 mm of pre-bend.